Risk factors for earlier dementia onset in autopsy‐confirmed Alzheimer's disease, mixed Alzheimer's with Lewy bodies, and pure Lewy body disease. Issue 3 (11th February 2020) - Schaffert, Jeff; LoBue, Christian; White, Charles L.; Wilmoth, Kristin; Didehbani, Nyaz; Lacritz, Laura; Nguyen, Trung; Peters, Matthew E.; Fields, Lindy; Li, Chengxi; Cullum, C. Munro
Abstract: Introduction: Clinical Alzheimer's disease (AD) and dementia with Lewy bodies often have mixed AD and Lewy pathology, making it difficult to delineate risk factors. Methods: Six risk factors for earlier dementia onset due to autopsy‐confirmed AD (n = 647), mixed AD and Lewy body disease (AD + LBD; n = 221), and LBD (n = 63) were entered into multiple linear regressions using data from the National Alzheimer's Coordinating Center. Results: In AD and AD + LBD, male sex and apolipoprotein E ( APOE ) ɛ4 alleles each predicted a 2‐ to 3‐year‐earlier onset and depression predicted a 3‐year‐earlier onset. In LBD, higher education predicted earlier onset and depression predicted a 5.5‐year‐earlier onset. Discussion: Male sex and APOE ɛ4 alleles increase risk for earlier dementia onset in AD but not LBD. Depression increases risk for earlier dementia onset in AD, LBD, and AD + LBD, but evaluating the course, treatment, and severity is needed in future studies.